WEB-BASED INSTRUCTION IN TEACHING LISTENING SKILL AT SMAN 1 PANGKEP - Fitrizah, Luthfiyyah Ainur; Salija, Kisman; Jafar, Muhammad Basri (Universitas Negeri Makassar, 2024)
This research investigates the implementation of web-based instruction in teaching listening skills in Indonesian Senior high school students. The research aims to describe and find out the three following objectives: 1) The implementation of web-based instruction in the teaching listening process 2) Describe teacher’s perception of the implementation Web-Based Instruction in teaching listening in Indonesian EFL Classrooms 3) Describe students’ perception of the impact web-based instruction in developing listening skill in EFL Classroom. This research applied descriptive qualitative research with a case study approach. The population of this research were students of XII Bahasa SMAN 1 Pangkep and used purposive sampling to obtain samples from a population. The sample of this research was selected by interviewing the teacher taught by using web-based instruction in teaching listening. The data was collected by observation and interview. The result of this research shows that 1) The implementation of WBI in the teaching listening process as a medium instructional, utilization of interactive activity, and promote autonomous learning 2) Teacher’s perception of the implementation of WBI in EFL classrooms discovered giving positive impact on teaching process can be seen teacher can use as medium instruction in teaching English, access authentic material, give online interactive activities and promote autonomous learning. 3) students’ perception of the impact of the implementation of WBI in teaching English listening skills to students in several aspects accessibilities, increased engagement, promoting collaborative learning, and flexibility used.